2020
DOI: 10.1016/j.cnp.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Bitemporal independent 3-Hz spike-and-waves in adult patient with idiopathic generalized epilepsy and Graves disease

Abstract: Highlights Seizures are known to be one of the neurological complications of thyrotoxicosis. We report unusual bitemporal independent 3-Hz spike-wave activity in a patient with IGE and Graves disease. We speculate that thyroid dysfunction superimposed on IGE thalamocortical network oscillations resulted in this EEG pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Furthermore, the case also demonstrated bitemporal independent lateralized 3-Hz spike-and-wave activity. 10 The observed EEG alterations in individuals with hyperthyroidism, such as diffuse, bilateral, or regional slowing, heightened fast activity, elevated alpha-rhythm frequency, and modified responsiveness to photic stimulation, suggest a potential interaction between thyroid dysfunction and thalamocortical network oscillations in idiopathic generalized epilepsy. This interaction may ultimately lead to a decreased seizure threshold and the initiation of epileptic episodes.…”
Section: The Role Of Thyroid Hormones In Cns and Epilepsy Thyroid Hor...mentioning
confidence: 99%
“…Furthermore, the case also demonstrated bitemporal independent lateralized 3-Hz spike-and-wave activity. 10 The observed EEG alterations in individuals with hyperthyroidism, such as diffuse, bilateral, or regional slowing, heightened fast activity, elevated alpha-rhythm frequency, and modified responsiveness to photic stimulation, suggest a potential interaction between thyroid dysfunction and thalamocortical network oscillations in idiopathic generalized epilepsy. This interaction may ultimately lead to a decreased seizure threshold and the initiation of epileptic episodes.…”
Section: The Role Of Thyroid Hormones In Cns and Epilepsy Thyroid Hor...mentioning
confidence: 99%
“…4 GTCS is characterized by muscle contractions and sudden loss of consciousness, 5,6 with generalized spikewave discharge. 7,8 Moreover, in patients with GTCS, widespread abnormal functional activity has been detected throughout the brain, 9 and it has been suggested that both primary and high-order brain networks are involved. 10,11 Most GTCSs can be effectively controlled by antiseizure medications (ASMs).…”
Section: Introductionmentioning
confidence: 99%
“…Generalized tonic–clonic seizures (GTCS) is a type of epilepsy and accounts for 20%–55% of all epilepsies 4 . GTCS is characterized by muscle contractions and sudden loss of consciousness, 5,6 with generalized spike–wave discharge 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Generalized tonic-clonic seizures (GTCS) is a type of epilepsy characterized by muscle contractions, sudden loss of consciousness (Jallon & Latour, 2005; Marini, King, Archer, Newton, & Berkovic, 2003), with generalized spike-wave discharge(GSWD) (Broutian et al, 2020;Li, Chen, & Huang, 2020). Until now, antiepileptic drugs (AEDs) are common treatments for epilepsy.…”
Section: Introductionmentioning
confidence: 99%